Association of dietary intake of saturated fatty acids with hypertension: 1999–2018 National Health and Nutrition Examination Survey - Gou, Ruoyu; Gou, Yufan; Qin, Jian; Luo, Tingyu; Gou, Qiannan; He, Kailian; Xiao, Song; Li, Ruiying; Li, Tingjun; Xiao, Jie; Chen, Ziqi; Chen, Yulu; et al. (Frontiers in Nutrition, 2022)
OBJECTIVE: This study aimed to assess the relationship between dietary intake of saturated fatty acid (SFA) and its subtypes (C4:0, C6:0, C8:0, C10:0, C12:0, C14:0, C16:0, C18:0) and hypertension. DESIGN, PARTICIPANTS, AND METHODS: Adults aged 20 years and older based used the U.S. Health and Nutrition Survey (1999–2018) were used as participants. Two averages of 24 h dietary recall data were obtained for weight-adjusted continuous cross-sectional analysis. A logistic regression model was used to estimate the weighted dominance ratio and its 95% confidence interval for hypertension. RESULTS: Of the 26,778 respondents aged 20 years and older, hypertensive patients had a hypertension prevalence of 35.06% and less (mean ± SD) dietary intake of SFA, C14:0, and C16:0 compared with normal subjects (P<0.0001). After adjusting for confounders, the second quartile of C12:0 (0.80 [0.66-0.96]) may be a protective factor for hypertension among respondents, and the third quartile of C12:0 (0.72 [0.56-0.93]) may be a protective factor for hypertension in men. In addition, an interaction was observed among C12:0, age, and hypertension, indicating that women consuming C16:0 dose at the second quartile (0.75 [0.56-1.00]) may be a protective factor for hypertension. An interaction was also observed between middle-aged respondents (45–64 years) and SFA on hypertension.